PENGEMBANGAN MEDIA LEARNING MANAGEMENT SYSTEM (LMS) BERBASIS KITĀB AL-‘ARABIYAH LI AN-NĀSYI’ĪN - Ridha, Muhammad Rasyid; Ayuni, Siti Khurotun; Shodiq, Muhammad Jafar (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
The speed of information and communication technology development influences the transition of all human life in various ways, including in education. These various development media are incomplete if there are no things that make it easier for everyone to access learning. One media that can facilitate learning, especially learning Arabic, is E-learning based on the Learning Management System (LMS). This study adopts R&D research (research and development) with five stages: analysis, design, development, implementation and evaluation. The trial (implementation stage) was carried out on class XI students at the Muhammadiyah Boarding School Modern Islamic Boarding School in Yogyakarta, with a total of 42 students. The research results are in the form of learning media products of Learning Management System (LMS) based on the Book of Al-̒Arabiyah Li An-Nāsyi'īn for class XI students at the Muhammadiyah Boarding School Modern Islamic Boarding School, Yogyakarta, which can be accessed on the website https://mbs-yogya.ucm.ac.id/courses/11-tamrin-lughoh. The validation results from media experts obtained a feasibility of 92 in the very feasible category, while material experts were 86 in the very feasible category. As for the trials from the students, the results were 92.56 with a very decent category and 86 with a very decent category from the teachers.Keywords: Development, Learning Media, Learning Management System, Al-̒Arabiyah Li An-Nāsyi'īn̒